Treating Depression, Anxiety, and Stress in Ethnic and Racial Groups: Cognitive Behavioral Approaches. 2018
DOI: 10.1037/0000091-011
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral models, measures, and treatments for stress disorders in Latinos.

Abstract: The tremendous growth in the Latino population in the United States has led to a surge of interest in understanding the mental health experiences of this population. This interest has also been spurred by the recognition that Latinos are affected by significant and persistent economic, educational, and mental health care disparities (Blanco et al., 2007;Gonzales & Papadopoulos, 2010). These disparities make it critical that the mental health community increase its understanding of the mental health experiences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…In Chang et al's (2018) volume regarding Latinx populations, Ngo and Miranda (2018) wrote about CBT for depression, Bernal et al (2018) discussed anxiety disorders, and Cardemil et al (2018) considered stress disorders. Specific to the literature on depression and Latin Americans, Ngo and Miranda (2018) reviewed the research on assessment tools and CBT.…”
Section: Cbt With Latinxmentioning
confidence: 99%
See 1 more Smart Citation
“…In Chang et al's (2018) volume regarding Latinx populations, Ngo and Miranda (2018) wrote about CBT for depression, Bernal et al (2018) discussed anxiety disorders, and Cardemil et al (2018) considered stress disorders. Specific to the literature on depression and Latin Americans, Ngo and Miranda (2018) reviewed the research on assessment tools and CBT.…”
Section: Cbt With Latinxmentioning
confidence: 99%
“…They discussed the impact of culture, language, cultural adaptation, and the accessibility of evidence-based treatments for anxiety for Latinx populations. Cardemil et al (2018) described culturally influenced acculturative stress and reviewed cognitive behavioral models, measures, and treatment of PTSD and acculturative stress for Latinos. They ended with a discussion of future directions for cognitive behavioral research and treatment of stress disorders for Latinos.…”
Section: Cbt With Latinxmentioning
confidence: 99%
“…Still, the overall research on Latinx children and families according to Bernal and Rodriguez (2009) was less than 0.005% of the publications in this area, an alarming fact given that Latinx are the largest ethnic minority in the US. Additionally, reviews of research in cognitive behavioral modalities aimed at addressing anxiety (Bernal et al 2018), stress (Cardemil et al 2018), and depression (Ngo and Miranda 2018) found a corresponding low level of research focusing on Latinx, and these are even lower for Spanish-speaking Latinx. Therefore, a sense of racism and exclusion is compounded by the fact that psychotherapeutic model efficacy-models that were created predominantly by White European Americans-is validated by research done on that same population.…”
Section: Latinx Needs Within Us Mental Healthmentioning
confidence: 99%
“…Research shows that prior trauma exposure is highly associated with post-traumatic stress disorder (PTSD). In addition, the negative effects of acculturative stress include a higher risk of mood and anxiety disorders (Cardemil et al 2018). Thus, Latinx are found to have a higher prevalence of symptoms for PTSD (Cardemil et al 2018).…”
Section: Trauma Treatment Among Latinx: Opportunities Within Psychotherapymentioning
confidence: 99%
See 1 more Smart Citation